2016
DOI: 10.1245/s10434-016-5536-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy for Adrenocortical Carcinoma: Is There a Therapeutic Benefit?

Abstract: Background Lymph node metastasis is an established predictor of poor outcome for adrenocortical carcinoma (ACC); however, routine lymphadenectomy during surgical resection of ACC is not widely performed and its therapeutic role remains unclear. Methods Patients undergoing margin-negative resection for localized ACC were identified from a multi-institutional database. Patients were stratified into 2 groups based on the surgeon’s effort or not to perform a lymphadenectomy as documented in the operative note. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 21 publications
1
44
0
1
Order By: Relevance
“…Intraoperative factors were obtained from the surgeon’s operative report (e.g., if a surgeon dictated that a LND was performed, this was recorded as such regardless of anatomic landmarks used as limits of dissection or number of lymph nodes removed). 23 The pathologic variables included tumor size, tumor weight, tumor-node-metastasis (TNM) stage, tumor grade, number of lymph nodes in the specimen, vein involvement, and margin status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative factors were obtained from the surgeon’s operative report (e.g., if a surgeon dictated that a LND was performed, this was recorded as such regardless of anatomic landmarks used as limits of dissection or number of lymph nodes removed). 23 The pathologic variables included tumor size, tumor weight, tumor-node-metastasis (TNM) stage, tumor grade, number of lymph nodes in the specimen, vein involvement, and margin status.…”
Section: Methodsmentioning
confidence: 99%
“…11,2022 Performance of lymph node dissection (LND) also may be associated with improved survival. 2325 …”
mentioning
confidence: 99%
“…According to large American and French series, approximately 10-30% of patients with ACC had formal lymphadenectomy as part of the tumor resection, reflecting the heterogeneity of operative management (25,198). A minimum of four lymph nodes should be retrieved in order to declare lymph node-negative cases (201) Furthermore, in an analysis of 120 cases identified from a multi-institutional database, the benefit of lymphadenectomy on overall survival persisted on multivariable analysis controlling for adverse preoperative and intraoperative factors associated with lymphadenectomy, such as tumor size, palpable mass, irregular tumor edges, suspicious nodes on imaging and multivisceral resection (202). The largest series so far included 283 patients and the resection of more than five lymph nodes reduced also the risk of local recurrence and disease-related death in a multivariate analysis (203).…”
Section: Reasoningmentioning
confidence: 99%
“…This is highlighted by the variety of definitions used to describe regional lymphadenectomy for ACC in studies evaluating its impact on prognosis and survival. 5,[12][13][14][15] Among these studies, reported rates of lymphadenectomy range from only 6% to 33%. 3,5,[12][13][14][15][16][17] Moreover, examination of any lymph nodes has been alarmingly low, with reported rates less than 35%.…”
Section: Introductionmentioning
confidence: 99%
“…5,[12][13][14][15] Among these studies, reported rates of lymphadenectomy range from only 6% to 33%. 3,5,[12][13][14][15][16][17] Moreover, examination of any lymph nodes has been alarmingly low, with reported rates less than 35%. 3,5,[12][13][14][15][16][17] Despite the low frequency of lymph node examination, nodal metastasis has been identified as an independent negative predictor of survival.…”
Section: Introductionmentioning
confidence: 99%